Analysis of Supporting and Inhibiting Factors of Students' Critical Thinking Ability at Islamic Elementary School - Amin Supartin (JENIUS (Journal of Education Policy and Elementary Education Issues), 2023)
This research is motivated by the many factors influencing students' critical thinking skills. The purpose of this study was to review the supporting and inhibiting factors for students' critical thinking skills at MIN 4 Sukoharjo, Kab. Sukoharjo, Central Java. This research is descriptive with the type of qualitative research and data collection through interviews and observation. The resource person interviewed was one of the class VI teachers at MIN 4 Sukoharjo. The research showed several supporting and inhibiting factors for students' critical thinking skills at MIN 4 Sukoharjo. The results of the research are in the form of supporting factors for students' critical thinking skills as follows: (1) School facilities in the form of Indonesian Madrasah Competency Assessment/Asesmen Kompetensi Madrasah Indonesia (AKMI) books for class V; (2) Implementing the 2013 Curriculum; (3) School policies that free teachers to explore students, and (4) Selection of appropriate learning methods and models. Meanwhile, the results of the research were in the form of inhibiting factors for students' critical thinking skills as follows: (1) The facilities provided for those other than class V were only in the form of providing HOTS questions based on the subject by each teacher; (2) Teachers are less creative and innovative which causes learning activities to be not conducive; (3) the intellectual level of students and limited learning time, and (4) teachers do not master IT